Benny uncovers a mystery - Warner, Gertrude Chandler, 1890-1979.; Cunningham, David, 1938- (Niles, Ill. : A. Whitman, 1976)
Two brothers take summer jobs at a department store where a series of peculiar events brings them under suspicion.
Braille.
Keywords: Department stores -- Fiction; Mystery fiction